Changes in aerosol size distributions over the Indian Ocean during different meteorological conditions. Issue 1 (1st January 2020) - Kesti, Jutta; Asmi, Eija; O'Connor, Ewan J.; Backman, John; Budhavant, Krishnakant; Andersson, August; Dasari, Sanjeev; Praveen, Puppala S.; Zahid, H.; Gustafsson, Örjan
Abstract: Aerosol emissions in South Asia are large. The emitted aerosols can travel significant distances and, during the Asian southwest monsoon especially, are prone to modification through cloud processing and wet scavenging while being transported. The scale of emissions and transport means that the global climate impact of these aerosols are sensitive to modification en route, but the process-level understanding is still largely lacking. In this study, we analyse long-term aerosol data measured at an observatory established in Hanimaadhoo, Republic of Maldives, to investigate the long-term properties of aerosols over the Indian Ocean as well as to understand the effect of precipitation on the aerosol particle size distribution during long-range transport. The observatory location is ideal because it is a receptor site with little local influence, and, depending on the season, receives either polluted air masses coming from the Indian subcontinent or clean marine air masses from the Indian Ocean. We analysed the sub-micron particle number size distribution measured during the years 2004–2008, and 2014–2017, and this is the first inter-seasonal long-term study of the sub-micron aerosol features in the region. The aerosol origin and its relative exposure to wet scavenging during long-range transport were analysed using back-trajectory analysis from HYSPLIT. By comparing aerosol measurements to precipitation along its transport, this study shows that there is a substantial change in particle number size distributions and concentrations depending on the amount of rainfall during transport. During the southwest monsoon season, the aerosol size distribution was notably bi-modal and total particle concentrations clearly reduced in comparison with the prevailing aerosol size distribution during the northeast monsoon season. Precipitation during transport usually corresponded with a greater reduction in accumulation mode concentrations than for smaller sizes, and the shape of the median size distribution showed a clear dependence on the trajectory origin and route taken.